2018
DOI: 10.1088/1757-899x/349/1/012003
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Eugenol–Lauryl Methacrylate Copolymers via Cationic Polymerization

Abstract: Eugenol is one of the most abundant natural resources in Indonesia. The recently bio-based polymer resin is created based on eugenol because eugenol is functionalized with the polymerizable group. In order to improve the functional properties of eugenol, in this research Eugenol–Lauryl Methacrylate copolymers (co-poly(Eg-LMA)) were synthesized by cationic polymerization using H2SO4 as an initiator under the nitrogen atmosphere. Structure identification of the copolymer showed the absorption of the vinyl group … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 6 publications
0
4
0
Order By: Relevance
“…The proton NMR showed that the chemical shift at 3.92 ppm is a proton signal of the methoxy­(−O–CH 3 ) group. The identification of successful polymerization processes in poly­(eugenol sulfone) was demonstrated by the loss proton signal of the vinyl eugenol group at 5.00–6.00 ppm, and the appearance of chemical shifts at 1.00–2.50 ppm, which are proton signals for a double bond from a vinyl group that changes to a single bond . Based on the above identification, it is known that poly­(eugenol sulfone) has been successfully synthesized. , …”
Section: Resultsmentioning
confidence: 96%
“…The proton NMR showed that the chemical shift at 3.92 ppm is a proton signal of the methoxy­(−O–CH 3 ) group. The identification of successful polymerization processes in poly­(eugenol sulfone) was demonstrated by the loss proton signal of the vinyl eugenol group at 5.00–6.00 ppm, and the appearance of chemical shifts at 1.00–2.50 ppm, which are proton signals for a double bond from a vinyl group that changes to a single bond . Based on the above identification, it is known that poly­(eugenol sulfone) has been successfully synthesized. , …”
Section: Resultsmentioning
confidence: 96%
“…Data analysis and processing were performed using Map Info 9.0 software. The research results showed that the most ideal shape is trapezium made from soil with a cross-sectional area of 0.86 m 2 , the upper channel width of 1.5 m, the width of the canal base 0.65 m, 1.05 m high, and slope 45° [23].…”
Section: Scope Of Problemmentioning
confidence: 99%
“…There are a few examples of cationic copolymerization of eugenol in the literature. Eugenol and lauryl methacrylate copolymers were obtained by Fajrin et al 215 by cationic polymerization using sulfuric acid as initiator. On the other hand, Breloy et al 216 reported the synthesis of a biobased antibacterial coating using both cationic and thiol− ene reaction with eugenol and mono-and diepoxy limonene and with β-carotene as photosensitizer under visible-light irradiation.…”
Section: Eugenol-based Polymersmentioning
confidence: 99%